A rare case of thyroglossal duct cyst extending to the sublingual space: A case report. Issue 17 (April 2020) - Park, Mi Jung; Shin, Hwa Seon; Choi, Dae Seob; Choi, Hye Young; Choi, Ho Cheol; Lee, Sang Min; Jang, Jeong Ho; Lee, Jeong-Hee; Park, Jung Je; Park, Sung Eun
Abstract: Rationale: Thyroglossal duct cyst (TGDC) is the most common congenital anomaly of midline neck masses. A thyroglossal duct cyst is especially difficult to diagnose and is treated differently when it appears in the sublingual area. Here, we report a rare case of TGDC extending to the sublingual space. Patient concerns: A 42-year-old female presented with a history of neck swelling in the submental region. Diagnosis: The final pathologic diagnosis was a TGDC. Interventions: Sistrunk operation was performed. Outcomes: Recurrence of the disease has not been seen for the past year. Lession: Clinical awareness of the thyroglossal duct cyst in the sublingual area or on the oral floor area is important for an accurate diagnosis and the appropriated management.